On Two Specifications of Asset Equilibrium in Macroeconomic Models - Foley, Duncan K. (Journal of Political Economy, 1975)
The problem of specifying asset market equilibrium conditions in a macroeconomic model is studied. Two specifications are proposed: "beginning-of-period" and "end-of-period" formulations in period models. In each case the limit of the model as the time period is shortened is rigorously calculated. It is shown that the two formulations are internally consistent, but consistent with each other only under assumptions of perfect foresight. A brief review of the liquidity preference versus loanable funds literature shows that theorists have used these models without explicitly noting the differences and inconsistencies.